SOLIDARITAS DI MASA PANDEMI MENURUT PANDANGAN MAHASISWA STABN SRIWIJAYA - DL, Jatayu Jiwanda (Jurnal Agama Buddha dan Ilmu Pengetahuan, 2022)
This research is a qualitative descriptive study that focuses on exploring the views of Sriwijaya STABN students regarding solidarity during the pandemic. This is based on the difficult situation of the pandemic requires us to survive. So that one of the efforts that we can do together is to do solidarity. Solidarity must be carried out by all levels of society, including universities and students. The aim of this research is to describe solidarity during the pandemic in the view of Sriwijaya STABN students. The method used for data collection is observation, interviews and documentation. Through the three focuses of the study: meaning, form and benefits of solidarity during a pandemic, an illustration is obtained that the meaning of solidarity during a pandemic according to Sriwijaya STABN students are embracing and caring for the other condition. This is based on the understanding that we need each other and are in the same vulnerable, difficult and boring situation Keywords: pandemic, solidarity, caring, humanity